2020
DOI: 10.31234/osf.io/bya75
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tears Trigger the Intention to Offer Social Support: A Systematic Investigation of the Interpersonal Effects of Emotional Crying Across 36 Countries

Abstract: Tearful crying is a ubiquitous and mainly human phenomenon. The persistence of this behavior throughout adulthood has fascinated and puzzled many researchers. Scholars have argued that emotional tears serve an attachment function: Tears are thought to act as a social glue that binds individuals together and triggers social support intentions. Initial experimental studies supported this proposition across several methodologies, but these were typically conducted only across Western participants, resulting in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Further, various situational or contextual factors may also influence the effect of tears, and the image of a tearful immigrant male used in our study leaves it open to interpretation as to why the man is crying (see Zickfeld et al, 2020) It is likely that our participants attributed the crying to a personal tragedy (e.g., losing family members on the journey or leaving family behind). However, the same tears might produce different reactions in a perceiver if they are shown as manipulative (e.g., when caught by police or during an immigration interview).…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…Further, various situational or contextual factors may also influence the effect of tears, and the image of a tearful immigrant male used in our study leaves it open to interpretation as to why the man is crying (see Zickfeld et al, 2020) It is likely that our participants attributed the crying to a personal tragedy (e.g., losing family members on the journey or leaving family behind). However, the same tears might produce different reactions in a perceiver if they are shown as manipulative (e.g., when caught by police or during an immigration interview).…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…A systematic investigation across 41 countries Both everyday experience and scientific research show that the adaptive role of emotional tears goes far beyond their intrapersonal functions (Gračanin et al, 2018;Vingerhoets et al, 2000). Studies demonstrated that tears act as a social glue that bonds individuals together by fostering approach tendencies and eliciting the intention to support the crier (Van de Ven et al, 2017;Vingerhoets et al, 2016;Zickfeld et al, 2021). This interpersonal function of tears is driven by their impact on social perception.…”
Section: Tears Do Not Influence Competence In General But Only Under Specific Circumstancesmentioning
confidence: 99%
“…This interpersonal function of tears is driven by their impact on social perception. Specifically, tears have a positive effect on perceived warmth of the crier (Van de Ven et al, 2017;Zickfeld et al, 2021), a universal dimension of person perception that is intrinsically linked to human bonding, rapport, and affiliation (Fiske et al, 1999).…”
Section: Tears Do Not Influence Competence In General But Only Under Specific Circumstancesmentioning
confidence: 99%
See 2 more Smart Citations